Assessment of variceal pressure by continuous non-invasive endoscopic registration: a placebo controlled evaluation of the effect of terlipressin and octreotide. Issue 1 (January 1996) - Nevens, F; Van Steenbergen, W; Yap, S H; Fevery, J
Abstract : Octreotide has been proposed for the treatment of variceal bleeding. The effects on portal pressure, however, have been variable in published studies. As bleeding is more directly related to pressure in the varices, this study investigated the effect on variceal pressure of octreotide and terlipressin, a vasoactive drug with a well established effect. Variceal pressure was measured during four to eight minutes by a continuous non-invasive endoscopic registration method. Thirty patients in whom a stable variceal pressure recording had been obtained during at least one minute, were randomised to receive either 2 mg terlipressin, 50 micrograms octreotide or an identical volume of saline, as a single intravenous injection given over 60 seconds. For the final analysis three patients had to be excluded because of lack of a satisfactory recording. There were no significant clinical differences between the three groups of patients. Placebo administration did not induce significant changes, but a mean decrease in variceal pressure of -27% was noted with terlipressin, starting from two minutes onwards. Variceal pressure changes after injection of octreotide were variable and the mean change in pressure did not reach statistical significance. Seven of 10 patients showed a temporary increase in variceal pressure. In conclusion, terlipressin induces a significant and progressive decrease in variceal pressure but inconsistent variations of variceal pressure changes were seen after octreotide administration. This is probably related to its effect on central venous pressure. This study also shows that continuous variceal pressure recording with the non-invasive endoscopic registration technique detects in an accurate way the effect of vasoactive drugs on variceal pressure, because placebo injection did not produce significant changes.